2019
DOI: 10.3390/en12152848
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effect of Cobalt Additive on the Low Temperature Oxidation Characteristics of Changqing Tight Oil and Its SARA Fractions

Abstract: Air flooding is a potential enhanced oil recovery (EOR) method to economically and efficiently develop a tight oil reservoir due to its sufficient gas source and low operational costs, during which low temperature oxidation (LTO) is the key to ensuring the success of air flooding. In addition to inefficiency of conventional LTO, air flooding has seen its limited applications due to the prolonged reaction time and safety constraints. In this paper, a novel air injection technique based on the catalyst-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…By analyzing the target well P34-P6 of refracturing, the average effective thickness h e was 2.3 m, the average porosity was 12.5 %, the average permeability K was 1.32 mD (The standard deviation was 1.0766), the footage L of the horizontal well was 840 m, the drilling rate of oil-bearing sandstone D r was 84.9 %, the formation pressure P i was 20.4 MPa, and the oil saturation S o was 0.56. In the initial fracturing of well X-6, 9 clusters were fractured, the fracture spacing was 100 m, the initial fracturing fluid consumption was 14,400 m 3 , and the fracturing sand amount was 460 m 3 . After the initial fracturing, the average daily fluid level was 32 t, and the average daily oil production level was 10 t, and a good oil increase effect was achieved in the early stage of fracturing.…”
Section: Field Test and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the target well P34-P6 of refracturing, the average effective thickness h e was 2.3 m, the average porosity was 12.5 %, the average permeability K was 1.32 mD (The standard deviation was 1.0766), the footage L of the horizontal well was 840 m, the drilling rate of oil-bearing sandstone D r was 84.9 %, the formation pressure P i was 20.4 MPa, and the oil saturation S o was 0.56. In the initial fracturing of well X-6, 9 clusters were fractured, the fracture spacing was 100 m, the initial fracturing fluid consumption was 14,400 m 3 , and the fracturing sand amount was 460 m 3 . After the initial fracturing, the average daily fluid level was 32 t, and the average daily oil production level was 10 t, and a good oil increase effect was achieved in the early stage of fracturing.…”
Section: Field Test and Resultsmentioning
confidence: 99%
“…Tight oil is a key component of unconventional oil and gas resources and has great potential for exploitation [1]. Volume fracturing has become the core technology to develop tight oil and gas reservoirs [2][3][4]. However, with the development of depletion development, the decline of formation pressure causes fracture closure failure, resulting in a rapid decline of production and low recovery of a single well.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that organometallic catalysts promoted LTO reactions by increasing the generation rate of organic peroxides and decreasing the E a of LTO. Wang and Wang also reported that cobalt naphthenate reduced the E a of LTO reactions of light oil and its SARA fractions, and promoted the generation of hydroxyl-containing oxides and CO 2 in the LTO of saturates, aromatics, and resins. Although these organometallic salts were investigated, their oil-dispersed properties that might lead to a higher catalytic activity have been rarely emphasized or realized.…”
Section: Catalytic Oxidation Of Crude Oil Oxidationmentioning
confidence: 95%
“…After fracturing, the well is shut in for approximately 40-60 days to ensure permeability equilibrium before production is resumed. High-efficiency re-fracturing flooding integration technology encompasses flow field reconstruction, fracturing operations, and crude oil replacement [25]. Flow field reconstruction begins with a thorough recharge of the pre-pressurized zone, involving the injection of substantial volumes of oil-repellent fracturing fluids.…”
Section: High-efficiency Re-fracturing Flooding Integration Processmentioning
confidence: 99%